False-Positive Cholesteatomas on Non-Echoplanar Diffusion-Weighted Magnetic Resonance Imaging. Issue 5 (June 2020) - Muhonen, Ethan G.; Mahboubi, Hossein; Moshtaghi, Omid; Sahyouni, Ronald; Ghavami, Yaser; Maducdoc, Marlon; Lin, Harrison W.; Djalilian, Hamid R.
Abstract : Objectives: To investigate false-positive findings on non-echoplanar (non-EPI) diffusion-weighted magnetic resonance imaging (DWI) in patients under surveillance post-cholesteatoma surgery. Study Design, Setting, Subjects, and Methods: A retrospective review was performed on patients diagnosed with cholesteatoma who underwent surgical resection and were then followed by serial non-EPI DWI using half-Fourier acquisition single-shot turbo spin echo (HASTE) sequence. All patients had at least two annual follow-up imaging studies. Results: False-positive findings were identified in four patients. The size of the suspected lesions was 4 to 12 mm. Otoendoscopy was used during all primary cases and Argon laser was used in one case. In all cases, the entire cholesteatoma was removed, and no residual disease was detected at the end of the procedures. One patient underwent revision surgery but only cartilage graft was found in the area of concern. All patients had stable or resolved hyperintense areas in the subsequent HASTE sequences. Conclusion: False positive findings can occur with non-EPI DWI MRI and patients need to be counseled accordingly before revision surgery. Decreasing intensity and dimension of a suspected lesion and a positive finding in an area other than the location of the initial cholesteatoma may favor a false positive. If a false positive finding is suspected when the surgeon is confident of complete resection of the cholesteatoma, an MRI can be repeated in 6 to 12 months to assess changes in the dimension and intensity of the area of concern. Cartilage grafts may cause restricted diffusion on DWI sequences.